Reporter - Metzgar, Eric (United States : Stick Figure Productions, 2008)
Nicholas Kristof is the two-time Pulitzer Prize-winning columnist for The New York Times. In the summer of 2007, Kristof traveled to the darkest areas of conflict and poverty in the Democratic Republic of the Congo, a country in the midst of a humanitarian crisis. To date, 5.4 million people have been killed in Congo over the last decade. But Nick knows that statistics deaden his readers' interest and compassion. So to get the world to care, he goes in search of individuals whose stories will reflect the country's desperate crisis and mobilize readers worldwide. He journeys through ravaged villages and displacement camps, and makes a harrowing visit to Congo's reigning rebel warlord, General Nkunda, at his jungle hideout.
Keywords: Documentary films